Pengaruh Panjang Tali, Massa dan Diameter Bandul Terhadap Periode dengan Variasi Sudut - Yuli Yanti; Neng Nenden Mulyaningsih; Dandan Luhur Saraswati (Universitas Indraprasta PGRI Jakarta, 2020)
In basic physics practicums there are some simplification of cases that aim to support the understanding of physics learning concepts. In practicum implementation there is a proof process that is carried out through an experiment and involves a formulation. This can be found in simple pendulum experiments, in which there are simplified cases that facilitate understanding of the factors that affect the pendulum period value. Therefore, this study aims to prove the value of the pendulum period based on experimental results and calculation data based on formulas. The experimental method used is to use simple pendulum props and observe the effect of pendulum mass, pendulum diameter, length of the rope, and angle deviation on the value of the pendulum period. The angle variations chosen were 15o, 30o and 45o. The results obtained show that at an angle of 15o, the magnitude of the period depends only on the value of the change in the length of the rope, while at an angle of 30o and 45o, the magnitude of the angle affects the value of the period. The pendulum mass and pendulum diameter do not affect the magnitude of the period for all angular variations. Period values obtained based on experimental results and formula calculations do not show significantly different values.